Donor‐recipient age interaction and the impact on clinical results after heart transplantation. Issue 10 (2nd August 2020) - Lechiancole, Andrea; Vendramin, Igor; Sponga, Sandro; Guzzi, Giorgio; Ferrara, Veronica; Nalli, Chiara; Di Nora, Concetta; Bortolotti, Uberto; Livi, Ugolino
Abstract: To evaluate the impact of donor‐recipient age matching on clinical outcomes after heart transplantation, a total of 509 patients (January 1990‐December 2018, mean follow‐up 111 ± 80 months) were stratified into 4 groups ( young‐R/young‐D, young‐R/old‐D, old‐R/young‐D, old‐R/old‐D ) according to the recipient ( young‐R < 60, old‐R ≥ 60 years) and the donor ( young‐D < 50, old‐D ≥ 50 years) age. No difference was found among 30‐day mortality ( P = .11) and postoperative complications between groups. Both unadjusted and adjusted survival was significantly higher for group young‐R/young‐D than that of other groups, in which survival was similar [adjusted HR for mortality of 2.0(1.2‐3.4), 2.1(1.4‐3.8) and 2.5(1.6‐4.1) for groups old‐R/young‐D, young‐R/old‐D, old‐R/old‐D, respectively]. Compared to other groups, the incidence of grade ≥ 2 CAV was significantly lower in old‐R/young‐D group [adjusted HR 0.4(0.2‐0.7)]. Among young recipients, the rate of acute grade ≥ 2 rejection episodes was higher in those receiving an old donor graft ( P = .04). Old recipient groups were more affected by neoplasms and severe renal failure than young recipient groups ( P < .01). Employment of hearts from donors ≥50 years of age adversely affects survival in recipients <60 years of age but does not influence outcomes in older recipients. Also, donor and recipient ages seem to have opposite effects on incidence of rejections and CAV of high grade.